You are on page 1of 15

Further Pure 1

Revision Topic 3: Proof by induction


The OCR syllabus says that candidates should be able to:
(a) use the method of mathematical induction to establish a given result (not restricted to
summation of series);
(b) recognise situations where conjecture based on a limited trial followed by inductive proof is a
useful strategy, and carry this out in simple cases, e.g. to find the nth power of the matrix
1 1
0 1
_

,
.
Section 1: General principals
There are two steps involved in proving a result by induction:
Step 1: Prove true when n = 1.
Step 2: (The inductive step). Assume the result is true for n= k and then prove true for n = k + 1.
1.1 Summing series
Example: Prove by induction that
2
6
1
( 1)(2 1)
n
n
r
r n n

+ +

for all positive integer values of n.


Solution: We wish to show that
2 2 2 2
6
1 2 3 ... ( 1)(2 1)
n
n n n + + + + + + (*)
Step 1: This is to prove the result true when n = 1:
Left hand side of equation (*) = 1
2
= 1.
Right hand side of equation (*) =
1
6
(1 1)(2 1) + +
= 1.
So equation (*) is true when n = 1.
Step 2: We assume the result is true when n = k, i.e. we assume that
2 2 2 2
6
1 2 3 ... ( 1)(2 1)
k
k k k + + + + + +
We want to prove the result is true when n = k + 1, i.e. we wish to show that
2 2 2 2 2
1
6
1 2 3 ... ( 1) ( 1 1)(2( 1) 1)
k
k k k k
+
+ + + + + + + + + +
i.e.
2 2 2 2 2
1
6
1 2 3 ... ( 1) ( 2)(2 3)
k
k k k k
+
+ + + + + + + + .
But
2 2 2 2 2 2
6
1 2 3 ... ( 1) ( 1)(2 1) ( 1)
k
k k k k k + + + + + + + + + + (using our assumption).
So, [ ]
( 1) 2 2 2 2 2
6
1 2 3 ... ( 1) (2 1) 6( 1)
k
k k k k k
+
+ + + + + + + + +
Therefore,
( 1) ( 1) 2 2 2 2 2 2 2
6 6
1 2 3 ... ( 1) 2 6 6 (2 7 6)
k k
k k k k k k k
+ +
1
+ + + + + + + + + + +
]
Factorising we get:
2 2 2 2 2
1
6
1 2 3 ... ( 1) ( 2)(2 3)
k
k k k k
+
+ + + + + + + + as required.
Therefore the result is true for n = k + 1.
So, by induction, the result is true for all integers n 1.
Examination style question
Prove by induction that
2
1
( 1)
n
n
r
r n

for all positive integer values of n.


Worked examination question (AQA January 2006)
a) Prove by induction that
2 1
2 (3 2) (4 2 ) ... ( 1)2 2
n n
n n

+ + + + + (*)
for all integers n 1.
b) Show that
2
1 1
1
( 1)2 2 (2 1)
n
r n n
r n
r n
+
+
+

Solution:
Step 1: This is to prove the result true when n = 1:
Left hand side of equation (*) =
1 1
(1 1)2 2

+
Right hand side of equation (*) = 1 2
1
= 2.
So equation (*) is true when n = 1.
Step 2: We assume the result is true when n = k, i.e. we assume that
2 1
2 (3 2) (4 2 ) ... ( 1)2 2
k k
k k

+ + + + + .
We want to prove the result true when n = k + 1, i.e. we want to show that
2 1 1 1
2 (3 2) (4 2 ) ... ( 1 1)2 ( 1)2
k k
k k
+ +
+ + + + + + +
i.e. that
2 1 1
2 (3 2) (4 2 ) ... ( 1)2 ( 2)2 ( 1)2
k k k
k k k
+
+ + + + + + + + .
But,
2 1
2 (3 2) (4 2 ) ... ( 1)2 ( 2)2 2 ( 2)2
k k k k
k k k k

+ + + + + + + + + (using the assumption)


So
2 1
2 (3 2) (4 2 ) ... ( 1)2 ( 2)2 2 ( ( 2))
k k k
k k k k

+ + + + + + + + +
i.e.
2 1
2 (3 2) (4 2 ) ... ( 1)2 ( 2)2 2 (2 2)
k k k
k k k

+ + + + + + + +
i.e.
2 1
2 (3 2) (4 2 ) ... ( 1)2 ( 2)2 2 2( 1)
k k k
k k k

+ + + + + + + +
So we have
2 1 1
2 (3 2) (4 2 ) ... ( 1)2 ( 2)2 2 ( 1)
k k k
k k k
+
+ + + + + + + + as required.
Therefore the equation is true when n = k + 1.
So the equation is true for all integer values n 1.
b)
2 2
1 1 1
1 1 1
( 1)2 ( 1)2 ( 1)2
n n n
r r r
r n r r
r r r

+
+ + +

Using the result from part (a), we know that
2
1 2
1
( 1)2 2 2
n
r n
r
r n

and
1
1
( 1)2 2
n
r n
r
r n

.
Therefore,
2
1 2
1
( 1)2 2 2 2 2 2 2 2
n
r n n n n n
r n
r n n n n

+
+

Factorising gives:
2
1 1
1
( 1)2 2 (2 2 1) 2 (2 1)
n
r n n n n
r n
r n n
+
+
+

as required.
Examination question (OCR January 2005)
Prove by induction that
1
3
1 4 2 5 3 6 ... ( 3) ( 1)( 5) n n n n n + + + + + + +
for all integers n 1.
Examination question (Edexcel)
Prove, by induction, that
2
1
12
1
( 1) ( 1)( 1)(3 2)
n
r
r r n n n n

+ +

1.2 Sequences
Example: Prove that if
1
3 4 for
n n
u u n
+
+
, and
1
2 u
, then
1
4 3 2
n
n
u

.
Solution:
Step 1: We prove the formula true when n = 1:
1 1
1
4 3 2 4 2 2 u

(which is true).
Step 2: Assume the formula is true when n = k, i.e. that
1
4 3 2
k
k
u

.
We need to prove the result true when n = k + 1, i.e. that
1 1
1
4 3 2 4 3 2
k k
k
u
+
+
.
But,
1
1
3 4 3 4 3 2 4
k
k k
u u

+
1
+ +
]
(using the assumption).
So,
1
1
3 4 3 6 4 4 3 2
k k
k
u

+
+ as required.
Therefore the formula is true when n = k + 1.
Therefore the result is true for all integers n 1.
Examination question (AQA June 2005)
The sequence
1 2 3
, , ,... u u u
is defined by
1
1 1
2
0, ( ).
n n
u u u n
+
+
Prove by induction that, for all n 1,
( )
1
1
2
2.
n
n
u n

+
Worked examination question (Edexcel 2005)
(a) Express
3
10 6
+
+
x
x
in the form p +
3 + x
q
, where p and q are integers to be found.
(1)
The sequence of real numbers u
1
, u
2
, u
3
, ... is such that u
1
= 5.2 and u
n + 1
=
3
10 6
+
+
n
n
u
u
.
(b) Prove by induction that u
n
> 5, for n
+
.
(4)
Solution:
a) Note that p +
3 + x
q
=
( 3)
3
p x q
x
+ +
+
.
Writing
3
10 6
+
+
x
x
=
( 3)
3
p x q
x
+ +
+
, we must have 6x + 10 = p(x + 3) + q.
So 6 = p (comparing coefficients of x)
and 10 = 3p + q i.e. 10 = 18 + q i.e. q = -8.
Therefore
3
10 6
+
+
x
x
= 6 -
8
3 x +
.
b) u
n + 1
=
3
10 6
+
+
n
n
u
u
= 6 -
8
3
n
u +
.
Step 1: Prove the result true when n = 1, i.e. that u
1
> 5. This is trivially true as u
1
= 5.2.
Step 2: Assume true when n = k, i.e. that u
k
> 5.
We then need to prove the result true when n = k + 1, i.e. that u
k+1
> 5.
As u
k
> 5, then u
k
+ 3 > 8 and so
8
3
n
u +
< 1.
Therefore
u
n + 1
=
3
10 6
+
+
n
n
u
u
= 6 -
8
3
n
u +
> 6 1 = 5 (as required)
So the result is true when n = k + 1.
Therefore the result is true for n
+
.
Examination question (NICCEA)
Consider the sequence defined by the relationship
1
5 2
n n
u u
+
+
whose first term is
1
1 u
.
(i) Show that the first four terms are 1, 7, 37, 187,
(ii) Use the method of induction to prove that
1
1
2
3(5 ) 1
n
n
u

1

]
.
1.3 Divisibility
Some questions give you a formula that defines a sequence (in the form u
n
= f(n) ) and then ask
you to prove that all terms of the sequence are divisible by a particular number.
These questions are usually tackled by simplifying f(k + 1) f(k) OR f(k + 1) f(k).
Adapted past examination question (adapted MEI):
Let f(n) =
4 1
2 3
n+
+
. By considering f(n + 1) f(n), or otherwise, prove that
4 1
2 3
n+
+
is a
multiple of 5 for any positive integer n.
Solution: Let f(n) =
4 1
2 3
n+
+
.
Step 1: Prove f(1) is a multiple of 5. But f(1) =
5
2 3 +
= 35 (which is a multiple of 5).
Step 2: We assume f(k) is a multiple of 5. We want to prove that f(k + 1) is a multiple of 5.
First we try to simplify:
f(n + 1) - f(n) =
4( 1) 1
2 3
n+ +
+
- (
4 1
2 3
n+
+
) =
4 5 4 1
2 2
n n + +

=
4 1 4 4 1
2 (2 1) 15 2
n n + +

Therefore:
f(k + 1) f(k) =
4 1
15 2
k+

So, f(k + 1) =
4 1
15 2 ( )
k
f k
+
+ .
So, f(k + 1) is a multiple of 5.
Therefore by induction, f(n) must be a multiple of 5 for all positive integers n.
Worked Examination Question: Edexcel 2002
For n
+
prove that
2
3n + 2
+ 5
n + 1
is divisible by 3,
Solution:
Let f(n) = 2
3n + 2
+ 5
n + 1
If we here calculate, f(n + 1) + f(n) = 2
3(n+ 1) + 2
+ 5
n+ 1 + 1
+ (2
3n + 2
+ 5
n + 1
)
= 2
3n + 5
+ 5
n + 2
+ 2
3n + 2
+ 5
n + 1
= 2
3n + 5
+ 2
3n + 2
+ 5
n + 2
+ 5
n + 1
= 2
3n+2
(2
3
+ 1) + 5
n+1
(5 + 1)
= 9 2
3n+2
+ 6 5
n+1
Now we are ready to prove the result.
Step 1: First prove true when n = 1:
2
3 + 2
+ 5
1 + 1
= 32 + 25 = 57 (which is divisible by 3).
Step 2: Assume that the result is true when n = k, i.e. that f(k) is divisible by 3.
We showed above that f(k + 1) + f(k) = 9 2
3k+2
+ 6 5
k+1
i.e. that f(k + 1) = 9 2
3k+2
+ 6 5
k+1
f(k)
So f(k + 1) must be divisible by 3 (as required).
Therefore the result is true for n
+
Past examination question (AQA January 2004)
The function f is given by
3 3 3
( ) ( 1) ( 2) f n n n n + + + + .
a) Simplify, as far as possible, f(n + 1) f(n).
Divisible by 3 Divisible by 3
Divisible by 3 (by
assumption)
Multiple of 5
Assumed to be a
multiple of 5
b) Prove by induction that the sum of the cubes of three consecutive positive integers is divisible
by 9.
Past examination question (Edexcel 2003)
f(n) = (2n + 1)7
n
1.
Prove by induction that, for all positive integers n, f(n) is divisible by 4.
Past examination question (Edexcel)
f(n) =
4 4
24 2 3
n n
+
, where n is a non-negative integer.
a) Write down f(n + 1) f(n).
b) Prove by induction that f(n) is divisible by 5.
1.4 Matrix results
Example:
a) Find the matrices
2 3
1 1 1 1
and
0 1 0 1
_ _

, ,
.
b) Predict the value of
1 1
0 1
n
_

,
and prove your result true by induction.
Solution
a)
2
1 1 1 1 1 1 1 2
0 1 0 1 0 1 0 1
_ _ _ _


, , , ,
3
1 1 1 2 1 1 1 3
0 1 0 1 0 1 0 1
_ _ _ _


, , , ,
.
b) It seems sensible to predict that
1 1 1
0 1 0 1
n
n _ _


, ,
.
We know the result is true when n = 1, 2 and 3.
Suppose now that it is true when n = k, i.e. that
1 1 1
0 1 0 1
k
k _ _


, ,
.
We need to prove the result true when n = k + 1, i.e. that
1
1 1 1 1
0 1 0 1
k
k
+
+ _ _


, ,
.
But:
1
1 1 1 1 1 1 1 1 1
0 1 0 1 0 1 0 1 0 1
k k
k
+
_ _ _ _ _


, , , , ,
(by assumption)
Therefore:
1
1 1 1 1
0 1 0 1
k
k
+
+ _ _


, ,
(as required).
So the result is true for n = k + 1.
Therefore our prediction is true for all positive integer values of n.
Past examination question (MEI adapted)
You are given the matrix
1 4
1 3
_


,
A
.
(i) Calculate
2 3
and A A .
(ii) Prove by induction that
1 2 4
1 2
n
n n
n n
_


+
,
A
when n is a positive integer.
Past examination question (Edexcel 2002)
Prove that
n

,
_


4 9
1 2
=

,
_

+

1 3 9
3 1
n n
n n
when n is a positive integer.
Past examination question
Let
1 0
1 2
A
_

,
.
Use induction to prove that, for all positive integers n,
2
1 0
1 2 2
n
n
A
_

,
.
1.5 Other examination questions
Past examination question (OCR 2004)
(i) Show that
1 1
( ) ( )
k k k k k
x y x x y y x y
+ +
+ .
(ii) Using this result, prove by induction that (x y) is a factor of
n n
x y for all integers n 1.
Past examination question (OCR)
Prove by mathematical induction that, for all positive integers n,
1 1 1 1 1
... 1
2 4 8
2 2
n n
+ + + +

You might also like